2009
DOI: 10.1158/1940-6207.capr-09-0207
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Prevention Advances with a Translational Trial of Green Tea

Abstract: This perspective on Tsao et al. (beginning on p. 931 in this issue of the journal) discusses green tea extract, which was shown for the first time to have dose-dependent effects in a clinical chemopreventive setting (oral premalignant lesions). This translational trial provides important data on angiogenesis and other biomarkers on which to base future clinical research, which should include trials of green tea extract or polyphenols combined with other natural or synthetic compounds to enhance chemopreventive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In a prostate cancer (PCa) chemoprevention trial, green tea PPE did not reduce the likelihood of PCa in men with baseline high grade prostatic intraepithelial neoplasia and/or atypical small acinar proliferation, although the number of incidents of PCa was less in the treatment arm (27). These trials clearly demonstrate that green tea alone may not be sufficiently active for effective chemoprevention/therapy and the combination of green tea with other natural or synthetic agents has been suggested (24,25,28).…”
Section: Combination Of Resveratrol and Green Tea Epigallocatechin Gallate Induces Synergistic Apoptosis And Inhibits Tumor Growth In Vivmentioning
confidence: 88%
“…In a prostate cancer (PCa) chemoprevention trial, green tea PPE did not reduce the likelihood of PCa in men with baseline high grade prostatic intraepithelial neoplasia and/or atypical small acinar proliferation, although the number of incidents of PCa was less in the treatment arm (27). These trials clearly demonstrate that green tea alone may not be sufficiently active for effective chemoprevention/therapy and the combination of green tea with other natural or synthetic agents has been suggested (24,25,28).…”
Section: Combination Of Resveratrol and Green Tea Epigallocatechin Gallate Induces Synergistic Apoptosis And Inhibits Tumor Growth In Vivmentioning
confidence: 88%
“…Therefore, the crux is to find biomarkers for early detection of oral precancerous lesions and an effective, nontoxic and affordable novel pharmacological agent in clinical trials for preventing carcinogenesis and the development of squamous cell carcinoma (SCC) as well as second primary SCC. Preventing or treating oral premalignant lesion with natural products, such as salvianolic acid B (Sal-B), ,, green tea, genistein and scutellarin or synthetic chemical agents is now one of the most promising approaches to prevent oral cancer. , Extensive studies have suggested that Salvia miltiorrhiza (Danshen) can reduce the cancer development by inducing the immunomodulatory effect, the antioxidative activity via apoptosis and inhibiting the tumor cell proliferation . Sal-B, one of its bioactive component, can inhibit the oral cancer cell proliferation in vitro and the malignant transformation from OLK to OSCC in vivo and shows promise as a COX-2 targeted anticancer agent for head and neck SCC prevention and treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Topical application of green tea extract has shown to reduce thickness of oral leukoplakia. [14,15] Curcumin It is found in turmeric and gives protection against environmental dietary mutagens. Frequently used spices and herbs as antioxidants are rosemary, sesame seeds, pepper, chilli pepper and ginger.…”
Section: Mode Of Actionmentioning
confidence: 99%